Hubungan Postur Kerja dan Gerakan Berulang dengan Musculoskeletal Disorders (MSDs) pada Pekerja Pembuat Sol Sepatu di Mergelo Mojokerto - Cindy Felicia; Fariz Zuvil Arganata; Nafilatul Fitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Workers in the shoe sole making industry in Mergelo Mojokerto in carrying out the production process do work with unnatural postures that are carried out repeatedly. It was found that shoe sole workers experienced moderate and high Musculoskeletal Disorders. The purpose of this study, namely to analyze work postures and tenure with Musculoskeletal Disorders. This research method is quantitative cross sectional design with saturation sampling technique on 31 workers using spearman rank analysis of SPSS 26 application. The research instruments are Nordic Body Map (NBM), stopwatch, and Rapid Upper Limb Assessment (RULA). Based on the results of the analysis, the significance value of work posture with Musculoskeletal Disorders is 0.00 <0.05 and the significance value of repetitive motion with Musculoskeletal Disorders is 0.010 <0.05. Work posture and repetitive motion factors have a significant relationship with Musculoskeletal Disorders. This study suggests replacing work facilities that lack ergonomics and performing streching movements before performing work activities.